Pengaruh Struktur Aktiva, Perputaran Total Asset, Perputaran Aktiva Tetap, dan Laverage Terhadap Profitabilitas (ROA) - Bunga Roito br. Silalahi; Friska Darnawaty Sitorus; Rafiq Christiadi; Shelly Shelly; Debora Laia (Politeknik Ganesha Medan, 2022)
This study aims to see the effect of asset structure, total asset turnover (TATO), fixed asset turnover, leverage (DER) on profitability (ROA) in building construction sub-sector companies registered on the IDX (Indonesian Stock Exchange). The sample used in this study is the building construction sub-sector companies registered on the BEI for the 2015-2019 period. The population in the study were 20 companies in the building construction sub- sector. The purposive sampling technique used in this study has a total sample of eighteen companies in the building construction sub-sector with a sample of 90 data. The data analysis technique used is multiple linear regression analysis with SPSS 20 software. The results of the study state that the asset structure has a significant positive effect on profitability (ROA). Total asset turnover (TATO) has a significant effect on profitability (ROA). Fixed asset turnover has a significant effect on profitability (ROA). Leverage (DER) has a negative and insignificant effect on profitability (ROA).